New records of three closely identical species of Megaselia Rondani (DIPTERA: PHORIDAE) from Bangi, Selangor, peninsular Malaysia - Raja M. Zuha; L. Disney, R. Henry (Penerbit Universiti Kebangsaan Malaysia, 2023)
Megaselia nigella Beyer, 1960, Megaselia scabra Schmitz, 1926 and Megaselia shiyiluae Disney, 1995 were described for the first time from Bangi, Selangor, Peninsular Malaysia. All three species were collected from baited white pan traps with decomposed beef liver at a secondary forest of Forensic Science Simulation Site, Faculty of Health Sciences, Universiti Kebangsaan Malaysia (UKM), Bangi, Selangor. In the laboratory, the phorid specimens were dissected and mounted on microscope slides for species identification. Megaselia nigella, M. scabra and M. shiyiluae looked almost similar from gross examination, based on their small, dark bodies, short costal veins in both sexes and short anal tubes of the hypopygia in males. However, these species can be distinguished, among others, according to the disposition of bristles on frons in both sexes. The discovery of these three species brings the total number of Megaselia from Peninsular Malaysia to 34. The results can be used as precursors to further understand the diversity of Phoridae from this region.